A Review: Simulation and Optimization Modelling for CO2 Geological Storage - Cai, Yanpeng; Dong, Cong; Cai, Jianying (Journal of Environmental Accounting and Management, 2026)
As one of the most effective ways to reduce greenhouse gas emission in the short to medium terms, CO2 sequestration and storage has attracted much attention in many countries across the world. Due to the high potential capacity globally, geological storage of CO2 is considered as an applicable technology to a wide spectrum of geological sites. In this complex process, many economic, technical, political, and environmental factors are involved, causing conflicts among multiple objectives. Management of CO2 capture and storage is thus essential for analyzing tradeoffs among these objective, and reducing the associated risks to local communities. Although great efforts have been made, effective design and management of various CO2 storage systems, as well as analysis of associated risks are still challenging to practitioners. In recent years, simulation and optimization methods have been used for addressing important management problems of CO2 capture and storage. The combined simulation-optimization approaches can account for the complex behaviours of the storage process and can help identify the best management strategies under consideration of the management objectives and constraints, as well as the associated risks. During the past decades, a large number of studies were conducted to simulate CO2 flow and transport in the geological substrate, and seek cost-effective storage schemes. This paper presented a comprehensive review on recent developments, advancements, challenges, and barriers associated with simulation and optimization modeling approaches in supporting CO2 capture and geological storage. A number of methodologies and applications were examined. Perspectives of effective management schemes were investigated, demonstrating many demanding areas for enhanced research efforts, which included issues of data availability and reliability, concerns in uncertainty, necessity of post-modeling analysis, and usefulness of development of process control techniques.